Fabrication of nanodiamonds/polyaniline nanocomposite for bilirubin adsorption in hemoperfusion - Futao Wang; Xiangyun Zheng; Qi Zhao; Yuchen Feng; Guanyue Gao; Dalibor M. Stanković; Jinfang Zhi (Functional Diamond)
Carbon-based nanomaterials have been explored as effective adsorbents to remove bilirubin in hemoperfusion therapy. However, developing carbon-based absorbents with both high adsorption capacity and good hemocompatibility remains a challenge in clinical applications. In this study, an efficient adsorbent for bilirubin removal was fabricated by grafting polyaniline (PANI) onto nanodiamonds (NDs). The nanocomposite ND-PANI had negligible effect on the hemolytic activity, confirming its excellent blood compatibility. The adsorption results revealed that the ND-PANI had high adsorption capacities (947 mg/g) and rapid adsorption rate toward bilirubin. Moreover, it exhibited efficient bilirubin adsorption in bovine serum albumin (BSA) solution, indicating its potential for practical application. Additionally, the adsorption kinetics and isotherms were systematically analyzed and modeled, thereby offering insights into the possible adsorption mechanism. Our findings suggest that the ND-PANI could be used as an efficient sorbent for the bilirubin removal, offering a promising avenue for blood purification application.